Estimating the impact of imported malaria on local transmission in a near elimination setting: a case study from BhutanResearch in context - Kinley Wangdi; H Juliette T. Unwin; Kinley Penjor; Tsheten Tsheten; Tobgyal; Archie Clements; Darren Gray; Manas Kotepui; Samir Bhatt; Peter Gething (The Lancet Regional Health - Southeast Asia, 2024)
Summary: Background: Bhutan has achieved a substantial reduction in both malaria morbidity and mortality over the last two decades and is aiming for malaria elimination certification in 2025. However, a significant percentage of malaria cases in Bhutan are imported (acquired in another country). The aim of the study was to understand how importation drives local malaria transmission in Bhutan. Methods: Information on geo-located individual-level laboratory-confirmed malaria cases between 2016 and 2020 was obtained from the Bhutan Vector-borne Disease Control Program. Records included the date of diagnosis and treatment, type of cases classified as indigenous or imported, and malaria species. Hawkes Processes were used to study the role of imported malaria in local transmission in Bhutan. We imposed 15 days delay for a mosquito to become infectious in the model. Findings: There were 285 cases during the study period and 58.6% (159) were imported malaria. 71.1% (113) of these imported cases were Plasmodium vivax and 73.6% (117) were from India. The model suggested that a person remains infectious for 8 days for Plasmodium falciparum malaria but over 19 days for P. vivax. The background intensity from imported malaria cases was much greater for P. vivax cases (maximum 0.17) resulting in more importations than P. falciparum cases (maximum 0.06). However, model fitting suggested that local P. falciparum transmission was mainly driven by importations but additional factors such as relapse played a role for P. vivax. Interpretation: Imported malaria cases are key drivers of transmission within Bhutan, with most cases since 2016 being P. vivax. Control programmes should be devised to target interventions towards the P. vivax strain and test those who are more likely to bring in imported malaria cases or acquire it from returning travellers. Funding: None.